MATEMATIKA DALAM KURIKULUM SMK PASCA PANDEMI COVID-19 - Jero Budi Darmayasa; Shinta Wulandari; Lina Ervana (IKIP Siliwangi, 2023)
This study aims to find a substantive theory about learning a new paradigm for mathematics in the Vocational High School (SMK) curriculum in Bulungan District, North Kalimantan Province. To achieve this goal, the researcher chose a qualitative research method with a case study approach. The unit of analysis for this study is the school community (curriculum vice chief, mathematics teacher, and vocational students) who are carrying out the teaching and learning process at vocational schools. To obtain the necessary data, interviews, observations, and documentation analysis were carried out. The data obtained were then analyzed using the pattern matchmaking technique as recommended by Robert K. Yin. The findings of this study are that mathematics has a strategic position in the SMK curriculum. This strategic position is that there is a change in the position of mathematics from national content to the 2013 curriculum to vocational basics in the independent curriculum. In addition, learning mathematics in vocational schools still needs to be varied to achieve competencies that are expected to help students use facts, principles, concepts, and procedures that are relevant to their vocational skills.